Graphic Design and Strategy: A Biometric Analysis on Data for The Period 2000-2024 - Başgün, Ferda; Altunbey, Tuba (Prof.Dr. İskender AKKURT, 2024)
Graphic design has become a multidisciplinary field that goes beyond aesthetic concerns where art and technology are blended. For this reason, studies on graphic design and strategies in the Web of Science database were examined using bibliometric analysis. In the research, data such as types and numbers of publications, publication language, distribution of topics by years, authors' profile networks and number of connections, results of author collaborations, co-authorship analysis, keyword analysis, country analysis of publications and citation power were collected. The collected data were visualised in tables. In the research, it was observed that there has been an increase in the number of graphic design publications since 2010. Studies were more preferred especially in the fields of art, design and communication. It was also revealed that there are interdisciplinary connections in the studies. The study will be a valuable reference point for future research in the light of developments in the field of graphic design. In addition, the study will guide researchers who want to turn to new topics in the field of visual communication and graphic design. The field of graphic design can meet the needs of different disciplines. For this reason, the study will also shed light on interdisciplinary researchers. The results obtained will guide designers who need a design strategy, researchers who conduct interdisciplinary studies and visual artists. The results of the research will guide graphic design and interdisciplinary studies from a holistic perspective. It is also predicted that the data obtained will shed light on new research topics and make significant contributions to the literature. © IJCESEN.
Keywords: Bibliometric Analysis; Graphic Design; Strategy